Cripto favors chondrocyte hypertrophy via TGF‐β SMAD1/5 signaling during development of osteoarthritis. Issue 3 (6th September 2021) - Garcia de Vinuesa, Amaya; Sanchez‐Duffhues, Gonzalo; Blaney‐Davidson, Esmeralda; van Caam, Arjan; Lodder, Kirsten; Ramos, Yolande; Kloppenburg, Margreet; Meulenbelt, Ingrid; van der Kraan, Peter; Goumans, Marie‐José; ten Dijke, Peter
Abstract: Chondrocytes in mice developing osteoarthritis (OA) exhibit an aberrant response to the secreted cytokine transforming growth factor (TGF)‐β, consisting in a potentiation of intracellular signaling downstream of the transmembrane type I receptor kinase activin receptor‐like kinase (ALK)1 against canonical TGF‐β receptor ALK5‐mediated signaling. Unfortunately, the underlying mechanisms remain elusive. In order to identify novel druggable targets for OA, we aimed to investigate novel molecules regulating the ALK1/ALK5 balance in OA chondrocytes. We performed gene expression analysis of TGF‐β signaling modulators in joints from three different mouse models of OA and found an upregulated expression of the TGF‐β co‐receptor Cripto ( Tdgf1 ), which was validated in murine and human cartilage OA samples at the protein level. In vitro and ex vivo, elevated expression of Cripto favors the hypertrophic differentiation of chondrocytes, eventually contributing to tissue calcification. Furthermore, we found that Cripto participates in a TGF‐β–ALK1–Cripto receptor complex in the plasma membrane, thereby inducing catabolic SMAD1/5 signaling in chondrocytes. In conclusion, we demonstrate that Cripto is expressed in OA and plays a functional role promoting chondrocyte hypertrophy, thereby becoming a novel potential therapeutic target in OA, for which there is no efficient cure or validated biomarker. © 2021 The Authors. The Journal of Pathology published by John Wiley & Sons, Ltd. on behalf of The Pathological Society of Great Britain and Ireland.